Contrasting multiproxy reconstructions of surface ocean hydrography in the Agulhas Corridor and implications for the Agulhas Leakage during the last 345,000 years - Martinez-Mendez, Gema; Zahn, Rainer; Hall, Ian R.; Peeters, Frank J. C.; Pena, Leopoldo D.; Cacho, Isabel; Negre, Cesar (PALEOCEANOGRAPHY, 2010)
Planktonic delta(18)O and Mg/Ca-derived sea surface temperature (SST) records from the Agulhas Corridor off South Africa display a progressive increase of SST during glacial periods of the last three climatic cycles. The SST increases of up to 4 degrees C coincide with increased abundance of subtropical planktonic foraminiferal marker species which indicates a progressive warming due to an increased influence of subtropical waters at the core sites. Mg/Ca-derived SST maximizes during glacial maxima and glacial Terminations to values about 2.5 degrees C above full-interglacial SST. The paired planktonic delta(18)O and Mg/Ca-derived SST records yield glacial seawater delta(18)O anomalies of up to 0.8%, indicating measurably higher surface salinities during these periods. The SST pattern along our record is markedly different from a U(37)(K')-derived SST record at a nearby core location in the Agulhas Corridor that displays SST maxima only during glacial Terminations. Possible explanations are lateral alkenone advection by the vigorous regional ocean currents or the development of SST contrasts during glacials in association with seasonal changes of Agulhas water transports and lateral shifts of the Agulhas retroflection. The different SST reconstructions derived from U(37)(K') and Mg/Ca pose a significant challenge to the interpretation of the proxy records and demonstrate that the reconstruction of the Agulhas Current and interocean salt leakage is not as straightforward as previously suggested.